Current balance method of dual windings parallel coils based on distributed capacitor compensation in high‐power WPT systems. Issue 2 (20th October 2021) - Bie, Zhi; Wang, Chao; Song, Kai; Zhang, Jiantao; Zhu, Chunbo
Abstract: Dual windings parallel (DWP) coils are often used in high‐power wireless charging applications to reduce current stress and internal resistance. Due to the inconsistent self‐inductance and strong coupling of the two windings, the advantages of the DWP coils cannot be fully utilized. In particular, the current stresses of the two windings are different, which will cause one of the stress to exceed the limit, and the temperature rise is too high. The reason for the current imbalance in the two windings is analysed in this work, and a distributed capacitor compensation method is proposed to balance the current stress in the two windings. Finally, a WPT system with the DWP transmitting coil was built as an example to demonstrate the effectiveness of the proposed method. The experimental results show that the current ratio in two windings decreased from 1.70 to 1.05 after using the proposed compensation method.